A Case of Tuberculous Meningitis with Tuberculoma in Nonimmunocompromised Immigrant. (20th June 2016) - Rali, Parth; Arshad, Hammad; Bihler, Eric
Abstract : We present a case of tuberculous (TB) meningitis in nonimmunocompromised immigrant worker who initially presented with headache and later with generalized tonic clonic seizures and disseminated tuberculosis.